The face and consciousness of discrimination - Dores, A. P. (2018)
Does the facial expression of those discriminated reveal and denounce, or not, that they are being mistreated? When a woman, or a prisoner, says she fell down the stairs to explain a black eye, what credibility and attention does she deserve from neighbors, friends, authorities, and society? What is hidden behind such stereotyped explanations? How is it possible to hide the causes of what is and will be visible on the face for a few days, in the sight of all?